Psychology of Service and Relationship on Satisfaction and Loyalty of Diploma IV Cadets Boarded in Sekolah Tinggi Ilmu Pelayaran - Agung Kwartama; Rakesh Paul (Journal of Innovation in Educational and Cultural Research, 2025)
Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta, a maritime education institution, operates a boarding school system requiring cadets to reside in dormitories, enhancing learning efficiency and soft skills development. This research investigates the impact of service quality and relationship quality on cadet satisfaction and, subsequently, on cadet loyalty, a crucial factor for institutional success and graduate quality. Employing a causal relationship method, this study distributed 93 questionnaires, each having 32 statements, to STIP Jakarta cadets. Data analysis, utilizing SmartPLS, focused on descriptive statistics and hypothesis testing through Structural Equation Modeling (SEM). The study found that service and relationship quality positively affect cadet satisfaction. In addition, cadet satisfaction has a positive and significant on cadet loyalty. Relationship quality exerts a more substantial influence on satisfaction than service quality, and service quality indirectly impacts loyalty through the mediating role of satisfaction. This means that cadet satisfaction serves as a crucial link, that is, a mediator, between service aspects and cadet loyalty. The practical implication suggests that STIP Jakarta should prioritize fostering strong relationships and high satisfaction, with relationship quality particularly crucial. This study's contribution lies in providing empirical evidence within the specific context of a maritime boarding school that highlights the dominance of relationship quality in fostering cadet satisfaction and loyalty, offering insights that directly support strategic improvements in student experience management.